Bruxism frequency and dental occlusion type in a group of Mexican adolescents. - José Murrieta; Verónica Cielo; Josefina Morales; Carmen Sánchez; Celia Linares; Martha González (Journal of Oral Research, 2014)
Introduction. Bruxism is a parafunctional habit characterized by the incessant action of grinding and clenching of the teeth improperly. It can occurred when dental occlusion is altered due to premature contacts between the teeth, and excursive occlusal interference. These conditions can alter the frequency, intensity and duration of the bruxism episode adopted. A transversal study was carried out to evaluate the frequency of the habit of bruxism and its relation with the type of dental occlusion in a group of teenagers. Material and method. A total of 278 teenagers were examined, who were signed up in high school. For the epidemiology survey, a questioner was applied and they were given a mouth exam for such end, an examiner was previously standardized (malocclusion kappa=0.89, bruxism kappa=0.93). Results. 51.5% of the teenagers presented bruxism being more frequent in the category of 17 years old with no difference of sex. The 81.4% showed some kind of dental malocclusion, out of which 57.6% were cases of malocclusion Class I, the 21.4% Class II and the 2.4% Class III, with no association noticed between both variables. Conclusion. The frequency of bruxism was high with similar distribution given the age as well as gender with no relation noticed with the type of dental occlusion or with the frequency of dental malocclusion.